The calibration and application of a force-measuring apparatus on the seat of a rowing ergometer - Murphy, A. J.; Chee S. T. H.; Bull, A. M. J.; McGregor, A. H. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2010)
A calibration procedure was carried out to optimize the measurement accuracy of an application of force transducers to quantify the force magnitude and centre of pressure on the seat of a rowing ergometer. Known forces were applied to the system at specified locations, and the recordings were used to provide a solution in the least-squares sense for transforming the transducers` voltage outputs to meaningful data. After calibration, the system was capable of measuring force to within 2 N of the applied load, identifying the position of force application to within 1.1 mm, and was more accurate than other apparatus described in the literature. The potential of the instrumentation for examining aspects of rowing technique in elite athletes was also demonstrated.